Labeling and preliminary in vivo evaluation of the 5-HT7 receptor selective agonist [11C]E-55888. Issue 9 (1st May 2015) - Hansen, Hanne D.; Andersen, Valdemar L.; Lehel, Szabolcs; Magnussen, Janus H.; Dyssegaard, Agnete; Stroth, Nikolas; Kristensen, Jesper L.; Knudsen, Gitte M.; Herth, Matthias M.
Graphical abstract: Abstract: E-55888 has been identified as a selective serotonin 7 (5-HT7 ) receptor agonist. In this study, we describe the synthesis, radiolabeling and in vivo evaluation of [ 11 C]E-55888 as a radioligand for positron emission tomography (PET) imaging. [ 11 C]E-55888 was obtained by N-methylation of an appropriate precursor using [ 11 C]MeOTf in acetone at 60 °C giving isolated quantities in the range of 1.7–2.4 GBq. Studies in Danish Landrace pigs demonstrated that [ 11 C]E-55888 has good brain uptake, however, the distribution in the brain tissue was dominated by non-specific binding, as binding could neither be displaced by the structurally different 5-HT7 receptor ligand SB-269970 nor by self-block with unlabeled E-55888. Based on these data, [ 11 C]E-55888 does not show promise as a PET radioligand for imaging the 5-HT7 receptor in vivo.